ISOLASI DAN KARAKTERISASI TERPENOID DARI EKSTRAK ETIL ASETAT KULIT BATANG MERANTI KUNYIT (Shorea conica) - Mustika Furi (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2014)
Terpenoid Isolated and characterization of terpenoid from the ethyl acetate extract of stem bark of Shorea conica had been done by usingextraction, vacuum liquid chromatography and column chromatography methods. The aim of this research was to isolation and characterization thesecondary metabolites of stem bark of Shorea conica The research results obtained pure compound EA2 the form ofamorphoussolid coloredyellowish-white and has a melting point of 207oC-209oC, soluble in ethyl acetate with RF 0.5 in comparison eluent hexane:ethyl acetate 6: 4 whichpositive with reagent Liebermann-Bouchard. The spectroscopies UV data of this compound has an absorption maximum 0,236 at a wavelength of 202nm and IR spectroscopies data of this compound showed the presence of C-H aliphatic, C=O, CH2 and C-O. Indicated this compound as terp